Anterior cervical discectomy and interbody fusion with porous tantalum implant. Results in a series with long-term follow-up. (November 2016) - Papacci, Fabio; Rigante, Luigi; Fernandez, Eduardo; Meglio, Mario; Montano, Nicola
Highlights: We report the largest series of anterior cervical discectomy and fusion with porous tantalum cages implant. Patients operated at a single or double level were included. We found a statistically significant improvement of all evaluated scores. No major complications occurred post-operatively and at follow-up. Abstract: Few papers have been published about the anterior cervical discectomy and fusion (ACDF) with implant of porous tantalum cages. These studies included patients submitted to operation at a single level. To our knowledge, we report the results of the largest series of ACDF with implant of porous tantalum cages. Our series included patients operated at a single or double level with a long follow-up (FU). We also discuss the pertinent literature. Clinical and outcome data of 99 consecutive patients (47 men, 52 women) submitted to ACDF with implant of porous tantalum cages (Trabecular Metal TM-S Cervical Fusion Device, Zimmer Spine, Minneapolis, MN) from June 2007 to September 2012, were retrospectively reviewed. Mean FU was 67.47 ± 19.63 months. The changes in pain were assessed using the Visual Analogue Scale (VAS). Patients were evaluated pre-operatively and at FU with the Short Form-36 Score Health Survey Version 2.0 (SF-36v2) for Physical Health and Mental Health Scores and the Neck Disability Index. We globally found a statistically significant improvement of all evaluated scores. Patients operated at two levels experienced a statistically significant improvement of all scores, with no statistical difference compared to patients operated at one level. No major complications occurred post-operatively and at FU. Only one patient (operated at two level) experienced an infection during FU. We conclude that ACDF with porous tantalum cages is a safe procedure, with long term clinical benefits (also in patients operated at two levels) and a very low rate of complications.